Cardiovascular Risk Factor Trajectories Since Childhood and Cognitive Performance in Midlife: The Cardiovascular Risk in Young Finns Study. Issue 20 (18th May 2021) - Hakala, Juuso O.; Pahkala, Katja; Juonala, Markus; Salo, Pia; Kähönen, Mika; Hutri-Kähönen, Nina; Lehtimäki, Terho; Laitinen, Tomi P.; Jokinen, Eero; Taittonen, Leena; Tossavainen, Päivi; Viikari, Jorma S.A.; et al.
Abstract : Background: Cardiovascular risk factors, such as high blood pressure, adverse serum lipids, and elevated body mass index in midlife, may harm cognitive performance. It is important to note that longitudinal accumulation of cardiovascular risk factors since childhood may be associated with cognitive performance already since childhood, but the previous evidence is scarce. We studied the associations of cardiovascular risk factors from childhood to midlife, their accumulation, and midlife cognitive performance. Methods: From 1980, a population-based cohort of 3596 children (3–18 years of age) have been repeatedly followed up for 31 years. Blood pressure, serum lipids, and body mass index were assessed in all follow-ups. Cardiovascular risk factor trajectories from childhood to midlife were identified using latent class growth mixture modeling. Cognitive testing was performed in 2026 participants 34 to 49 years of age using a computerized test. The associations of the cardiovascular risk factor trajectories and cognitive performance were studied for individual cardiovascular risk factors and cardiovascular risk factor accumulation. Results: Consistently high systolic blood pressure (β=–0.262 SD [95% CI, –0.520 to –0.005]) and serum total cholesterol (β=–0.214 SD [95% CI, –0.365 to –0.064]) were associated with worse midlife episodic memory and associative learning compared with consistently low values. Obesity since childhood was associated with worse visual processing and sustained attention (β=–0.407 SD [95% CI, –0.708 to –0.105]) compared with normal weight. An inverse association was observed for the cardiovascular risk factor accumulation with episodic memory and associative learning ( P for trend=0.008; 3 cardiovascular risk factors: β=–0.390 SD [95% CI, –0.691 to –0.088]), with visual processing and sustained attention ( P for trend<0.0001; 3 cardiovascular risk factors: β=–0.443 SD [95% CI, –0.730 to –0.157]), and with reaction and movement time ( P for trend=0.048; 2 cardiovascular risk factors: β=–0.164 SD [95% CI, –0.318 to –0.010]). Conclusions: Longitudinal elevated systolic blood pressure, high serum total cholesterol, and obesity from childhood to midlife were inversely associated with midlife cognitive performance. It is important to note that the higher the number of cardiovascular risk factors, the worse was the observed cognitive performance. Therefore, launching preventive strategies against cardiovascular risk factors beginning from childhood might benefit primordial promotion of cognitive health in adulthood. Abstract : Supplemental Digital Content is available in the text.